A Educação de Jovens e Adultos - EJA na Escola Professora Edeli Mantovani, SINOP-MT : história, educação e cidadania - Valendolf, Silvio Cesar (2023)
The present dissertation investigates the Teaching of History in Adult and Youth Education (EJA) at the Professora Edeli Mantovani School in Sinop – MT, exploring the interconnection among the key elements of History, Citizenship, and Democracy. When approaching the Adult and Youth Education (EJA), we focus not only on the transmission of historical knowledge but also on the formation of conscious and participative citizens, essential elements for strengthening democratic pillars and reclaiming the civic conditions of these students. Using participatory qualitative research, we analyze pedagogical practices in Adult and Youth Education (EJA) that promote a critical understanding of History, identifying its influence on citizenship construction. We also emphasize the importance of developing educational strategies that empower young people to comprehend not only the past but also to actively participate in contemporary society. This study contributes to the advancement of the Adult and Youth Education (EJA), providing light on how the Teaching of History can be an effective instrument in training capable engaged citizens of contributing to the consolidation of democratic values in their communities and, consequently, in society at large.